2006
DOI: 10.1677/joe.1.06494
|View full text |Cite
|
Sign up to set email alerts
|

Novel fish hypothalamic neuropeptides stimulate the release of gonadotrophins and growth hormone from the pituitary of sockeye salmon

Abstract: We recently identified a cDNA encoding three novel fish hypothalamic neuropeptides, having LPXRF-NH 2 from the goldfish brain. In this study, to clarify the physiological functions of these three LPXRFamide peptides (gfLPXRFa-1, -2, and -3), we analysed the localisation and hypophysiotrophic activity of these peptides using sockeye salmon, Oncorhynchus nerka, in which immunoassay systems for several anterior pituitary hormones have been developed. gfLPXRFa-immunoreactive cell bodies were detected in the nucleu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
130
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(142 citation statements)
references
References 21 publications
11
130
1
Order By: Relevance
“…Considering the changes in GnIH mRNA during reproduction, we concluded that GnIH plays a negative role in regulating GtH in the common carp. The results are consistent to those for the zebrafish and goldfish (Qi et al, 2013;Zhang et al, 2010), but opposite to the results obtained for the grass puffer, tilapia, and salmon (Amano et al, 2006;Biran et al, 2014;Shahjahan et al, 2011). The differing results may be related to the protein sequence of common carp GnIH compared with those of the goldfish, zebrafish, grass puffer, and tilapia.…”
Section: Discussionsupporting
confidence: 43%
See 1 more Smart Citation
“…Considering the changes in GnIH mRNA during reproduction, we concluded that GnIH plays a negative role in regulating GtH in the common carp. The results are consistent to those for the zebrafish and goldfish (Qi et al, 2013;Zhang et al, 2010), but opposite to the results obtained for the grass puffer, tilapia, and salmon (Amano et al, 2006;Biran et al, 2014;Shahjahan et al, 2011). The differing results may be related to the protein sequence of common carp GnIH compared with those of the goldfish, zebrafish, grass puffer, and tilapia.…”
Section: Discussionsupporting
confidence: 43%
“…These results indicate the negative regulation of GnIH on GtH. However, when incubating sockeye salmon (Oncorhynchus nerka) pituitary cell with different doses of goldfish GnIH-I/II/III peptides, FSH, LH, and GH concentrations increased significantly (Amano et al, 2006). In the grass puffer (Takifugu niphobles), incubation of pituitary cells with different doses of goldfish GnIH-I resulted in an increase in FSH and LH mRNA levels (Shahjahan et al, 2011).…”
Section: Introductionmentioning
confidence: 91%
“…Similarly, the rat GnIH ortholog RFRP3 increases the levels of GH in plasma (Johnson et al 2007). In teleosts, gGnIH and the other two putative RFamide peptides stimulate the release of GH from cultured pituitary cells from male sockeye salmon (Amano et al 2006).…”
Section: Introductionmentioning
confidence: 98%
“…Goldfish (g) GnIH (LPXRFamide 3) exerts both stimulatory and inhibitory influences on basal goldfish gonadotrope functions in a season-dependent manner, as well as differentially modulating the effects of sGnRH-and cGnRHII-induced gonadotrope functions (Moussavi et al , 2013. On the other hand, zebrafish GnIH reduced serum LH levels in adult goldfish (Zhang et al 2010), whereas gGnIH elevated LH and FSH release from salmon pituitary cell cultures (Amano et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…We therefore designated this neuropeptide as gonadotropin-inhibitory hormone (GnIH; Tsutsui et al 2000). Subsequently, several neuropeptides which were closely related to GnIH were identified in the brains of other vertebrates, such as mammals (RFamide-related peptides (RFRPs), Fukusumi et al 2001, Yoshida et al 2003, Ubuka et al 2009a, frogs (frog GH-releasing peptide (fGRP), Koda et al 2002, Ukena et al 2003b; Rana RFamide (R-RFa), Chartrel et al 2002) and fish (goldfish (gf) LPXRFa, Sawada et al 2002b, Amano et al 2006. Thus, it is becoming clear that GnIH and its orthologs having a common C-terminal LPXRFa motif (LPXRFa peptides) are synthesized in the brain in a variety of vertebrates (for reviews, see , Tsutsui 2009, 2010, Tsutsui & Osugi 2009, Tsutsui et al 2010a.…”
Section: Introductionmentioning
confidence: 99%